Global supply chain and operations management a decision-oriented introduction to the creation of value - Ivanov, Dmitry 1978-; Tsipoulanidis, Alexander; Schönberger, Jörn (Springer Texts in Business and Economics, 2017)
This textbook presents global supply chain and operations management from a comprehensive perspective, combining value creation networks and interacting processes. It focuses on the operational roles in the networks and presents the quantitative and organizational methods needed to plan and control the material, information and financial flows in the supply chain. Each chapter of the book starts with an introductory case study. Numerous examples from various industries and services help to illustrate the key concepts. The book explains how to design operations and supply networks and how to incorporate suppliers and customers. As matching supply and demand is a core aspect of tactical planning, the book focuses on it before turning to the allocation of resources for fulfilling customer demands. Providing readers with a working knowledge of global supply chain and operations management, this textbook can be used in core, special and advanced classes. Therefore, the book targets a broad range of students and professionals involved with supply chain and operations management. Special focus is directed at bridging theory and practice.